Differences in the cellular composition of small versus large uterine fibroids. Issue 5 (November 2016) - Holdsworth-Carson, Sarah J; Zhao, Dong; Cann, Leonie; Bittinger, Sophie; Nowell, Cameron J; Rogers, Peter A W
Abstract : Uterine fibroids are clonally derived from a single cell; however, despite being monoclonal, the cellular phenotypes that make up uterine fibroids are heterogeneous consisting of predominantly smooth muscle cells (SMC) and fibroblasts. This raises the question as to when clonal cell differentiation occurs during fibroid development, and does this information provide clues about possible mechanisms regulating the growth process that leads to fibroids of symptom-causing size? This study investigated the differences in the cellular composition of fibroids by immunohistochemistry (IHC). A tissue microarray ( n  = 21 hysterectomy cases) was used for the investigation of large uterine fibroids and normal myometrium. An investigation of small fibroids (≤ 5mm) used a separate group of samples ( n  = 7 hysterectomy cases, total of n  = 17 fibroids). A panel of cell phenotypic markers was selected based on our previous in situ investigations and included aldehyde dehydrogenase 1 (ALDH1A1) and vimentin for different fibroblast sub-populations, smooth muscle actin (SMA) as a marker for SMCs, CD31 for endothelial cells and CD45 for leucocytes. Proliferating cell nuclear antigen (PCNA) was also studied to identify proliferating cells. The cellular composition of small fibroids differs significantly from large fibroids. Small fibroids are more cellular (increased cells/mm 2 ) than large fibroids, have more blood vessels and also have a higher ratio of SMC to fibroblasts than large fibroids. Large fibroids have more cell proliferation (measured by PCNA) and fewer leucocytes (measured by CD45) than adjacent myometrium, whereas small fibroids are less proliferative and have similar number of leucocytes to myometrium. Different cellular composition between fibroids of different sizes may provide important clues as to the mechanisms that drive fibroid growth.